Utilizing Environmentally Friendly Techniques for the Sustainable Control of Plant Pathogens: A Review - Maria Alexandra Cucu; Ravish Choudhary; Vojislav Trkulja; Shivani Garg; Slavica Matić (Agronomy)
Utilizing environmentally friendly techniques for pathogen control in agriculture is a sustainable and eco-friendly approach to managing crop diseases. These techniques leverage the natural environment and ecosystem dynamics to reduce pathogen pressure, minimize the use of chemical inputs, and promote long-term agricultural productivity. Key strategies include crop rotation, intercropping, and maintaining biodiversity, all of which disrupt pathogen life cycles and enhance soil health. Biological control, such as introducing natural antagonists like beneficial fungi or bacteria, suppresses pathogen populations while promoting plant resilience. Additionally, practices such as mulching, soil solarization, and water management optimize environmental conditions to limit the development and spread of pathogens. These techniques also contribute to integrated pest management by providing sustainable, cost-effective solutions that reduce chemical dependency and mitigate climate change and other environmental impacts. This review discusses the importance of utilizing environmentally friendly techniques, highlighting their advantages, practical challenges, and limitations in different agro-ecological settings, and their role in advancing sustainable agriculture.